Nanoimprint glue and preparation method thereof
Patent Information
- Application Number
- CN202511005691.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-21
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-07-21
AI Technical Summary
[0003]紫外纳米压印,相比于热压印虽然不需要高温高压等条件,但紫外纳米压印过程中,会存在一定程度的固化不完全,影响微纳结构的力学性能,在脱模过程中容易出现破损、残留残胶等情况;在对紫外固化后的光学材料做可靠性测试时,也会出现不同程度的微纳结构损伤或脱落等情况
[0007]As can be seen from the above technical solution, the nanoimprint adhesive proposed in the first aspect of this invention, by employing optical monomers and nanoparticles with specific symmetrical structures and phenyl sulfide groups, provides a certain material basis for the nanoimprint adhesive to have a high refractive index. Furthermore, the optical monomers contain (meth)acrylate groups, thus possessing two or more functionalities, enabling them to effectively participate in curing with other components to form macromolecules or cross-linked networks. This allows the cured adhesive to achieve high structural strength, facilitating nanoimprint demolding, and ensuring that the micro/nano structure remains intact and does not easily leave adhesive residue during demolding. Reliability testing was conducted... When cured, the micro-nano structure on the colloid can also remain relatively intact; the difference in refractive index between the nanoparticles and the optical monomers in this application is greater than 0.4, the refractive index of the optical monomers themselves is 1.63 to 1.67, then the refractive index of the nanoparticles is greater than 2.03. In this application, it is not necessary to add too many nanoparticles to make the refractive index of the cured nanoimprint adhesive reach 1.7 to 1.8; since only a certain amount of nanoparticles are needed, the entire nanoimprint adhesive can maintain good fluidity and coatability, so that the coating effect of the colloid is good and it is easy to fill into the mold for imprinting, which is conducive to improving the production yield.
Smart Images

Figure CN120909064B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanoimprint technology, and more particularly to nanoimprint adhesives and their preparation methods. Background Technology
[0002] Nano-imprint lithography (NIL) is a technique that uses nanoimprint lithography adhesives to transfer micro- and nano-structures from a template onto a material to be processed. During the imprinting process, the nanoimprint lithography adhesive acts as a "medium" for pattern transfer. The micro- and nano-structures on the template interact with the nanoimprint lithography adhesive, thus replicating the micro- and nano-structures proportionally onto the adhesive. Nanoimprint lithography mainly includes thermal imprinting, ultraviolet (UV) imprinting, and soft imprinting. UV imprinting primarily uses UV-curable UV nanoimprint lithography adhesives. After the colloid interacts with the template at room temperature, it is cured by UV light to form an optical material with micro- and nano-structures.
[0003] While UV nanoimprinting does not require the high temperature and pressure conditions of thermal embossing, it suffers from incomplete curing, affecting the mechanical properties of the micro / nano structures. This can lead to damage and residual adhesive during demolding. Reliability testing of UV-cured optical materials also reveals varying degrees of micro / nano structure damage or detachment. Furthermore, while nanoimprinting adhesives typically contain a higher proportion of inorganic particles to increase the refractive index, this reduces fluidity, hindering the interaction between the adhesive and the template's micro / nano structures during imprinting. This can result in dimensional deformation or significant parameter variations, impacting optical performance. It also affects the coatability of the nanoimprinting adhesive, leading to poor coating results and reduced production yield. Summary of the Invention
[0004] In view of this, the present invention proposes a nanoimprint adhesive and its preparation method, aiming to solve at least one of the aforementioned technical problems, improve the structural strength of the adhesive after curing, and have a high refractive index and easy coating properties.
[0005] The nanoimprinting adhesive proposed in the first aspect of this invention is prepared from the following raw materials: optical monomers, acrylate prepolymers, modified acrylate prepolymers, nanoparticles, photoinitiators, coupling agents, and diluents, wherein the general structural formula of the optical monomers is as follows:
[0006] Wherein, R1 is methyl or hydrogen, R2 is methyl or hydrogen, and the difference between the refractive index of the nanoparticle and the refractive index of the optical monomer is greater than 0.4.
[0007] As can be seen from the above technical solution, the nanoimprint adhesive proposed in the first aspect of this invention, by employing optical monomers and nanoparticles with specific symmetrical structures and phenyl sulfide groups, provides a certain material basis for the nanoimprint adhesive to have a high refractive index. Furthermore, the optical monomers contain (meth)acrylate groups, thus possessing two or more functionalities, enabling them to effectively participate in curing with other components to form macromolecules or cross-linked networks. This allows the cured adhesive to achieve high structural strength, facilitating nanoimprint demolding, and ensuring that the micro / nano structure remains intact and does not easily leave adhesive residue during demolding. Reliability testing was conducted... When cured, the micro-nano structure on the colloid can also remain relatively intact; the difference in refractive index between the nanoparticles and the optical monomers in this application is greater than 0.4, the refractive index of the optical monomers themselves is 1.63 to 1.67, then the refractive index of the nanoparticles is greater than 2.03. In this application, it is not necessary to add too many nanoparticles to make the refractive index of the cured nanoimprint adhesive reach 1.7 to 1.8; since only a certain amount of nanoparticles are needed, the entire nanoimprint adhesive can maintain good fluidity and coatability, so that the coating effect of the colloid is good and it is easy to fill into the mold for imprinting, which is conducive to improving the production yield.
[0008] The preparation method of the nanoimprint adhesive according to the aforementioned embodiments of the second aspect of the present invention includes the following steps: adding a diluent to a container, adding an optical monomer, an acrylate prepolymer, and a modified acrylate prepolymer to a protective gas, stirring and mixing to form a uniform first solution; stirring the first solution and adding a coupling agent and a photoinitiator, continuing to stir to form a uniform second solution; adding nanoparticles to the second solution and continuing to stir until uniform, then allowing it to stand; and encapsulating by pressure filtration to obtain the nanoimprint adhesive.
[0009] As can be seen from the above technical solutions, the preparation method of the nanoimprint adhesive proposed in the second aspect of the present invention ensures that the components are fully mixed, do not easily agglomerate, and can form a relatively uniform coating adhesive, which is convenient for subsequent coating and imprinting. The prepared nanoimprint adhesive is easy to use and ensures that it has the aforementioned properties of the nanoimprint adhesive.
[0010] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit the disclosure of the embodiments of the present invention. Attached Figure Description
[0011] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0012] Figure 1 This is a schematic flowchart of a method for preparing optical monomers according to some embodiments of the present invention;
[0013] Figure 2 These are the chemical reaction equations involved in step S110 during the preparation of optical monomers as proposed in some embodiments of the present invention;
[0014] Figure 3 These are the chemical reaction equations involved in step S120 during the preparation of optical monomers as proposed in some embodiments of the present invention;
[0015] Figure 4 These are the chemical reaction equations involved in step S130 during the preparation of optical monomers as proposed in some embodiments of the present invention;
[0016] Figure 5 This is a schematic flowchart of the preparation method of nanoimprint adhesive proposed in some embodiments of the present invention. Detailed Implementation
[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.
[0018] In related technologies, the UV nanoimprint adhesive used has a relatively weak structural strength. During the UV nanoimprinting process, it is easy to stick to the template, which makes the UV nanoimprint adhesive with micro-nano structure easily damaged after imprinting, thus reducing the production yield. At the same time, the residual adhesive adhering to the mold contaminates the template and makes it inconvenient for the template to be used again.
[0019] In related technologies, the refractive index of the monomer main component of the ultraviolet nanoimprint adhesive is not high. It is necessary to add more inorganic particles to increase the refractive index of the entire adhesive. The high content of inorganic particles reduces the fluidity of the adhesive, making it difficult to coat. It also prevents the adhesive from interacting well with the micro-nano structure of the template during the imprinting process, thus making it impossible to produce high-performance optical materials with micro-nano structures.
[0020] In view of this, the present invention proposes a nano-imprinting adhesive, which has a high refractive index after curing, is easy to apply and use, has high structural strength, is easy to imprint and demold, and greatly reduces the probability of residual adhesive on the template.
[0021] Where there is no conflict, the following embodiments and features can be combined with each other.
[0022] The nanoimprint adhesive of this application will now be described.
[0023] According to the present invention, a nanoimprinting adhesive is prepared from the following raw materials: optical monomers, acrylate prepolymers, modified acrylate prepolymers, nanoparticles, photoinitiators, coupling agents, and diluents. The general structural formula of the optical monomers is as follows:
[0024] Wherein, R1 is methyl or hydrogen, R2 is methyl or hydrogen, and the difference between the refractive index of the nanoparticle and the refractive index of the optical monomer is greater than 0.4.
[0025] As can be seen from the above, the nanoimprint adhesive proposed in this invention, by employing optical monomers with specific symmetrical structures, gives the optical monomers of this application a certain degree of flip-folding ability and toughness. Furthermore, since the optical monomers possess groups such as phenyl sulfide groups, unsaturated aromatic groups, sulfur atoms, and (meth)acrylate groups, the unsaturated aromatic groups exhibit a conjugation effect, resulting in high molar refractive index and low molar volume, thus enhancing the refractive index of the optical monomers. Sulfur atoms achieve high polarizability, thus possessing a high refractive index. The phenyl sulfide group itself possesses the structure of both sulfur atoms and benzene rings, combining the conjugation effect of benzene rings with the high polarizability of sulfur atoms, effectively ensuring the refractive index of the optical monomers. The (meth)acrylate groups exhibit high refractive index and low volume shrinkage properties, thus the optical monomers of this application possess a high refractive index, measured to be 1.63–1.67. Nanoparticles with a refractive index difference greater than 0.4 from the optical monomers have a refractive index higher than 2.0. The raw materials containing these two components provide a certain material basis for the overall high refractive index of the nanoimprint adhesive.
[0026] Furthermore, since the acrylate groups in this application have C=C double bonds, which are relatively active, the optical monomers have two or more functionalities, enabling them to participate in curing with other components to form macromolecules or cross-linked networks. This allows the cured colloid to achieve high structural strength, which is beneficial for nanoimprint demolding. Moreover, the micro-nano structure remains intact and is not prone to leaving colloid residues during demolding. During reliability testing, the micro-nano structure on the cured colloid also remains relatively intact.
[0027] Since the refractive index of the optical monomer with the above-mentioned structure in this application is 1.63 to 1.67, and the difference between the refractive index of the nanoparticles and the optical monomers is greater than 0.4, the refractive index of the nanoparticles used in this application is greater than 2.03. Both the optical monomers and the nanoparticles have high refractive indices, so this application does not need to add too many nanoparticles to achieve a refractive index of 1.7 to 1.8 after curing. Since only a certain amount of nanoparticles are added, the refractive index and flowability of the nanoimprint adhesive are taken into account, so that the entire nanoimprint adhesive can maintain good flowability and coating properties, resulting in good coating effect of the adhesive and easy filling into the mold for imprinting during the imprinting process. In particular, it can fully fill the micro-nano structure of the mold, so that the nanoimprint adhesive has a complete micro-nano structure, improving the accuracy of imprinting and improving the production yield of nanoimprint adhesive with micro-nano structure.
[0028] In this application, the addition of acrylate prepolymer serves as a framework, facilitating the formation of a cross-linked network on the framework by other components. This provides the necessary mechanical strength and improves thermal stability for the cured nanoimprint adhesive. Modified acrylate prepolymers can enhance the abrasion resistance and leveling properties of the nanoimprint adhesive, with different properties being improved depending on the specific type added. Adding a photoinitiator allows for the absorption of ultraviolet light to generate free radicals or cations, triggering the curing of the acrylate monomers and prepolymers. This facilitates photocuring under ultraviolet light, improving curing efficiency. Adding a coupling agent enhances the adhesion of the nanoimprint adhesive to the substrate, effectively reducing the probability of the cured nanoimprint adhesive being peeled off during demolding. Adding a diluent ensures uniform dispersion, appropriate concentration, and suitable viscosity of all components in the colloidal system, facilitating coating and filling into the micro / nano structures within the template during the imprinting process.
[0029] Understandably, compared to related technologies where UV nanoimprinting adhesives tend to adhere to the template during UV nanoimprinting, leading to easy damage to the micro-nano structured adhesive and reduced production yield, this invention offers a superior solution. Furthermore, residual adhesive on the mold contaminates the template, hindering its reuse. The nanoimprinting adhesive of this invention boasts high structural strength, ensuring the formed micro-nano structure remains intact during demolding and maintaining a certain production yield. It also reduces residual adhesive on the mold, facilitating mold reuse.
[0030] Compared to related technologies where the main monomer component of the UV nanoimprint adhesive has a low refractive index, requiring the addition of a large number of inorganic particles to increase the overall refractive index of the adhesive, the high content of inorganic particles reduces the fluidity of the adhesive, making it difficult to coat and hindering its interaction with the micro-nano structure of the template during the imprinting process, thus preventing the fabrication of high-performance optical materials with micro-nano structures. The nanoimprint adhesive of this invention has a high refractive index and requires less inorganic particles, making it easy to coat and fill the micro-nano structure of the entire mold during the imprinting process.
[0031] In some embodiments of this application, the weight parts of each component in the raw material of the nanoimprint adhesive are as follows:
[0032] First component: 10 to 20 parts of optical monomer, for example, 10, 11, 14, 15, 17, 19 and 20 parts, etc.
[0033] Second component: 5 to 10 parts of acrylate prepolymer, for example, 5, 6, 7, 8, 9 and 10 parts, etc.
[0034] The third component is 5 to 10 parts of modified acrylate prepolymer, for example, 5, 6, 7, 8, 9, and 10 parts.
[0035] The fourth component consists of 20 to 35 parts of nanoparticles, for example, 20, 21, 23, 25, 26, 29, 30, 31, 32, 33, 34, and 35 parts.
[0036] Fifth component: 3 to 5 parts of photoinitiator, for example, 3.0 parts, 3.2 parts, 3.3 parts, 3.5 parts, 3.6 parts, 3.8 parts, 3.9 parts, 4.0 parts, 4.2 parts, 4.5 parts, 4.6 parts and 5.0 parts, etc.
[0037] Component 6: 1 to 5 parts of coupling agent, for example, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 3.7 parts, 4 parts, 4.5 parts and 5 parts, etc.
[0038] Component 7: 15 to 55 parts of diluent, for example, 15, 20, 32.2, 33, 39, 40, 52, 53 and 55 parts, etc.
[0039] Because nanoimprint adhesives require a high refractive index, and the main components contributing to this high refractive index are optical monomers and nanoparticles, the content of these two components needs to be relatively high. Furthermore, to maintain the flowability of the nanoimprint adhesive, the amount of nanoparticles added cannot exceed 35 parts; for example, in some specific embodiments, the amount of nanoparticles added is 25 parts. Since diluents are used to improve the viscosity and flowability of the entire adhesive system, their usage is also relatively high. Because acrylate prepolymers and modified acrylate prepolymers play a role in the curing framework of the nanoimprint adhesive and its properties such as abrasion resistance and leveling after curing, their usage needs to be appropriate. Photoinitiators and coupling agents mainly play an auxiliary role, so only a small amount is needed.
[0040] In some specific embodiments, by weight, the raw materials in the nanoimprint adhesive contain 15 parts of optical monomer, 8 parts of acrylate prepolymer, 8 parts of modified acrylate prepolymer, 25 parts of nanoparticles, 3 parts of photoinitiator, 1 part of coupling agent, and 40 parts of diluent.
[0041] In some specific embodiments, by weight, the raw materials in the nanoimprint adhesive contain 10 parts of optical monomer, 5 parts of acrylate prepolymer, 5 parts of modified acrylate prepolymer, 30 parts of nanoparticles, 4 parts of photoinitiator, 5 parts of coupling agent, and 41 parts of diluent.
[0042] In some specific embodiments, by weight, the raw materials in the nanoimprint adhesive include 20 parts of optical monomer, 10 parts of acrylate prepolymer, 10 parts of modified acrylate prepolymer, 35 parts of nanoparticles, 5 parts of photoinitiator, 5 parts of coupling agent, and 15 parts of diluent.
[0043] In some specific embodiments, by weight, the raw materials in the nanoimprint adhesive contain 12 parts of optical monomer, 6 parts of acrylate prepolymer, 6 parts of modified acrylate prepolymer, 21 parts of nanoparticles, 3.3 parts of photoinitiator, 3.7 parts of coupling agent, and 48 parts of diluent.
[0044] In some specific embodiments, by weight, the raw materials in the nanoimprint adhesive contain 17 parts of optical monomer, 9 parts of acrylate prepolymer, 7 parts of modified acrylate prepolymer, 29 parts of nanoparticles, 3.8 parts of photoinitiator, 2 parts of coupling agent, and 32.2 parts of diluent.
[0045] The amount of each component added can also be any other number of parts within the range of addition, which will not be elaborated here.
[0046] The structure and preparation method of the first component of the nanoimprint adhesive of this application are described below.
[0047] In some embodiments of this application, the optical monomer comprises monomers with the following four structural formulas:
[0048] Monomer 1 Monomer II
[0049] Monomer 3 Monomer IV
[0050] The preparation method of the self-made optical monomers of this application is described below. Since the preparation methods of the four monomers are similar, the preparation method of monomer one is mainly described. For monomer two, only epichlorohydrin in step S110 needs to be replaced with methyl epichlorohydrin; for monomer three, only acryloyl chloride in step S130 needs to be replaced with methacryloyl chloride; for monomer four, only epichlorohydrin in step S110 needs to be replaced with methyl epichlorohydrin, and acryloyl chloride in step S130 needs to be replaced with methacryloyl chloride. The related products are changed accordingly, which will not be elaborated here.
[0051] In some examples of the present invention, references Figure 1 As shown, monomer one in the optical monomer is prepared by the following steps: steps S110, S120 and S130.
[0052] Step S110: Refer to Figure 2 As shown, 4-methylthiobenzylthiophenol, the first catalyst and the first solvent are mixed evenly, and epichlorohydrin is added to react and generate the first product, which is 1-(4-methylthiobenzylthiool)-3-chloro-2-propanol.
[0053] In this step, a nucleophilic substitution reaction mainly occurs. 4-Methylthiobenzylthiophenol attacks the terminal carbon of the epoxy ring of epichlorohydrin under the action of the first catalyst, and ring-opening is performed to generate the first product 1-(4-methylthiobenzylthiool)-3-chloro-2-propanol.
[0054] It should be noted that when methyl epichlorohydrin reacts with 4-methylthiobenzylthiophenol, the first product is 1-(4-methylthiobenzylthiool)-3-chloro-2-methyl-2-propanol.
[0055] Step S120, Reference Figure 3 As shown, 4',4-dimercaptodiphenyl sulfide, a second catalyst, and a second solvent are mixed evenly, and the first product is added to catalyze the reaction to generate a second product. The molar ratio of the first product to 4',4-dimercaptodiphenyl sulfide is (2-2.4):1, and the second product is 4-4'-thiobis(1-(4-methylthiophenylthiol)-2-propanol) phenyl sulfide.
[0056] In this step, under the action of a second catalyst, the two thiol groups of 4',4-dimercaptodiphenyl sulfide attack an equivalent amount of chlorine atoms in the first product, thereby generating a second product with a symmetrical structure.
[0057] It should be noted that if methyl epichlorohydrin is used in step S110 to generate the first product, the second product will be 4,4'-thiobis(1-(4-methylthiophenylthiol)-2-methyl-2-propanol) phenyl sulfide. It should also be noted that the molar ratio of the first product to 4',4-dimercaptodiphenyl sulfide is (2–2.4):1, which can be 2:1, 2.2:1, 2.4:1, etc., ensuring that both moles of thiol groups are fully reacted to generate a more symmetrical second product.
[0058] Step S130, refer to Figure 4 As shown, the second product, auxiliaries, and stabilizers are added to the third solvent and mixed thoroughly. The solution is cooled, and acryloyl chloride is added under gas protection to react with the third catalyst to produce the product with the following structural formula: The optical monomer (monomer one) is wherein the molar ratio of acryloyl chloride to the second product is (2-2.4):1, for example, it can be 2:1, 2.2:1, 2.4:1, etc., so that both molar amounts of alcohol hydroxyl groups can be fully reacted to generate a third product with a more symmetrical structure, which is the optical monomer of this application.
[0059] In this step, the acylation reaction mainly occurs, in which the second product with the alcohol hydroxyl group attacks the carbonyl carbon of acryloyl chloride under the action of an auxiliary agent, a third catalyst and a stabilizer, and forms a side chain acrylate group after the chlorine is eliminated.
[0060] It should be noted that if methyl epichlorohydrin is used in step S110 to generate the first product, the second product is 4-4'-thiobis(1-(4-methylthiophenylthiol)-2-methyl-2-propanol) phenyl sulfide. If acryloyl chloride is used in step S130, monomer two with the aforementioned structural formula can be obtained. If methacryloyl chloride is used in step S130, monomer three with the aforementioned structural formula can be obtained. If methyl epichlorohydrin is used in step S110 to generate the first product, the second product is 4-4'-thiobis(1-(4-methylthiophenylthiol)-2-methyl-2-propanol) phenyl sulfide. If methacryloyl chloride is used in step S130, monomer four with the aforementioned structural formula can be obtained.
[0061] In some embodiments of this application, the first and second catalysts are selected from at least one of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (DBN), and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD). These types of catalysts can promote nucleophilic reactions. Specifically, in step S110, a proton can be abstracted from the thiol group to generate a highly reactive thiol anion, enhancing nucleophilicity. The thiol anion selectively attacks the less sterically hindered terminal carbon of the epichlorohydrin to generate a chloroalcohol intermediate (the first product). Specifically, in step S120, two protons can be abstracted from the thiol groups to generate a highly reactive dithiol anion, further enhancing nucleophilicity. The dithiol anion attacks the carbon atom of the halide to form a thioether bond. DBU is inexpensive and readily available, and can perform a mild ring-opening reaction on the epoxy substrate.
[0062] In some embodiments of this application, the first solvent and the second solvent are selected from at least one of toluene, dimethyl sulfoxide, N,N-dimethylformamide, and acetonitrile. The first solvent needs to be able to fully dissolve 4-methylthiophenethiophenol, the first catalyst, and epichlorohydrin (or methyl epichlorohydrin), so that all three can be fully mixed and reacted in the reaction system, which is beneficial for a more thorough reaction and promotes efficient reaction. Similarly, the second solvent needs to be able to fully dissolve the first product, 4',4-dimercaptodiphenyl sulfide, and the second catalyst, so that all three can be fully mixed and reacted in the reaction system, which is beneficial for a more thorough reaction in step S120 and promotes efficient reaction.
[0063] In some embodiments of this application, the additive is selected from triethylamine (TEA) or 1,8-diazabicycloundec-7-ene (DBU). The additive here can enhance the deprotonation activity of the alcohol hydroxyl group of the second product, thereby facilitating the attack on acryloyl chloride (or methacryloyl chloride) to generate a tetrahedral intermediate, and then release chlorine to form the optical monomer of this application.
[0064] In some embodiments of this application, the stabilizer is selected from at least one of butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), and tert-butylhydroquinone (TBHQ). These stabilizers effectively prevent the self-polymerization of acryloyl chloride, keeping it stable during the reaction, reducing side reactions, and ensuring the stability of the acrylate groups generated after the reaction of propyl acryloyl chloride, making them less susceptible to oxidation. This guarantees the stability of the nanoimprint adhesive made using optical monomers as a component. In particular, BHT is readily available, allowing for controllable reaction costs.
[0065] In some embodiments of this application, the third solvent is selected from dichloromethane or tetrahydrofuran. The third solvent can make the second product, auxiliaries, stabilizers, acryloyl chloride (or methacryloyl chloride) and the third catalyst mix evenly, making the reaction system more homogeneous, which is beneficial to improving the reaction efficiency and making the reaction more complete.
[0066] In some embodiments of this application, the third catalyst is 4-dimethylaminopyridine (DMAP). DMAP enables the reaction to proceed rapidly under mild conditions, avoids side reactions caused by high temperatures, and improves the purity of the reaction.
[0067] In some embodiments of this application, the molar ratio of 4-methylthiophenethiophenol, the first catalyst, the first solvent, and epichlorohydrin is 100:(70-90):(1317-1505):(100-120), for example, specific ratios of 100:70:1317:100, 100:80:1410:110, or 100:90:1505:120. Similarly, the molar ratio of 4-methylthiophenethiophenol, the first catalyst, the first solvent, and methyl epichlorohydrin is 100:(70-90):(1317-1505):(100-120), for example, specific ratios of 100:70:1317:100, 100:80:1410:110, or 100:90:1505:120. This allows the reaction in step S110 to be more complete and faster, the nucleophilic substitution reaction to be more thorough, and the byproducts to be reduced.
[0068] In some embodiments of this application, the reaction temperature of 4-methylthiophenthiophenol with epichlorohydrin or methyl epichlorohydrin is room temperature, and the reaction time is 14h to 18h, for example, 14h, 15h, 16h, 17h, or 18h, etc., without limitation. Nucleophilic reactions occurring at room temperature can effectively reduce the generation of byproducts and decrease the decomposition of heat-sensitive compounds.
[0069] In some embodiments of this application, the molar ratio of 4',4-dimercaptodiphenyl sulfide, the second catalyst, the second solvent, and the first product is 50:(50-55):(847-1035):(100-120), for example, 50:53.5:941:100, 50:53.5:941:110, 50:53.5:941:120, 50:50:847:100, 50:55:1035:120, etc. This allows the nucleophilic reaction in step S120 to be more complete and faster, the nucleophilic substitution reaction to be more thorough, byproducts to be reduced, and the formation of a dithiolated product.
[0070] In some embodiments of this application, the reaction temperature of 4',4-dimercaptodiphenyl sulfide with the first product is room temperature, and the reaction time is 18h to 22h, for example, 18h, 19h, 20h, 21h, or 22h, etc., without limitation. Nucleophilic reactions occurring at room temperature can effectively reduce the generation of byproducts and decrease the decomposition of heat-sensitive compounds.
[0071] In some embodiments of this application, the molar ratio of the second product, auxiliary agent, stabilizer, third solvent, acryloyl chloride, and third catalyst is 35:(144-187.2):(1.5-2.0):(1714-2026):(70-84):(3.0-4.0), for example, 35:175:1.75:1870:70:3.5, 35:175:1.75:1870:77:3.5, 35:175:1.75:1870:84:3.5, 35:144:1.5:1870:70:3.0, 35:187.2:2.0:2026:87:4.0. Alternatively, the molar ratio of the second product, auxiliaries, stabilizers, third solvent, methacrylamide chloride, and third catalyst can be 35:(144–187.2):(1.5–2.0):(1714–2026):(70–84):(3.0–4.0), for example, 35:175:1.75:1870:70:3.5, 35:175:1.75:1870:77:3.5, 35:175:1.75:1870:84:3.5, 35:144:1.5:1870:70:3.0, or 35:187.2:2.0:2026:87:4.0. This allows the acylation reaction in step S130 to be more complete and faster, reduces byproducts, and generates acrylate groups with a molecular weight of two.
[0072] In some embodiments of this application, the reaction temperature of the second product with acryloyl chloride or methacryloyl chloride is 0°C or under ice bath conditions, and the reaction is carried out under a protective atmosphere with nitrogen or inert gas, which can effectively prevent the decomposition of acryloyl chloride (or methacryloyl chloride) and make the reaction less likely to generate byproducts.
[0073] In some specific embodiments, reference is made to Figures 2 to 4 The reaction steps, and Figure 1 The specific operations for preparing the aforementioned monomer one in steps S110 to S130 are as follows:
[0074] 100 mmol of 4-methylthiobenzylthiophenol was mixed with 12 mL of DBU (80 mmol) in 150 mL of toluene (1.41 mol) and added to a 250 mL round-bottom flask equipped with a magnetic stir bar. The mixture was stirred for 30 minutes. Subsequently, 8.6 mL of epichlorohydrin (110 mmol) was slowly added dropwise. The reaction vessel was stirred at room temperature for 16 hours. Afterward, the volatiles were removed under reduced pressure, and the residue was diluted with DCM and washed successively with 1 M hydrochloric acid (100 mL), distilled water (100 mL), and brine (50 mL). The mixed organic extract was dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using a mixture of 20% ethyl acetate (EtOAc) in hexane as the eluent, ultimately yielding a colorless, low-viscosity liquid containing 1-(4-methylthiobenzylthiophenol)-3-chloro-2-propanol.
[0075] 50 mmol of 4',4-dimercaptodiphenyl sulfide was mixed with 8 mL of DBU (53.5 mmol) in 100 mL of toluene (941 mmol) and added to a 250 mL round-bottom flask equipped with a magnetic stir bar. The mixture was stirred for 30 minutes. Subsequently, 8.2 mL of 1-(4-methylthiophenylthiol)-3-chloro-2-propanol (110 mmol) was slowly added dropwise. The reaction vessel was stirred at room temperature for 20 hours. Afterward, the volatiles were removed under reduced pressure, and the residue was diluted with DCM and washed successively with 1 M hydrochloric acid (100 mL), distilled water (100 mL), and brine (50 mL). The mixed organic extract was dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using a mixture of 20% ethyl acetate (EtOAc) in hexane as the eluent, ultimately yielding a pale yellow viscous liquid containing 4,4'-thiobis(1-(4-methylthiophenylthiol)-2-propanol) phenyl sulfide.
[0076] 35 mmol of 4,4'-thiobis(1-(4-methylthiophenylthiol)-2-propanol)phenyl sulfide, 175 mmol of triethylamine, and 1.75 mmol of butylated hydroxytoluene (BHT) were added to a 250 mL round-bottom flask equipped with a magnetic stir bar. The solution was diluted with 120 mL of dichloromethane and stirred for 30 minutes under argon protection. After cooling the solution to 0 °C, 77 mmol of acryloyl chloride was added dropwise under argon protection, followed by 3.5 mmol of 4-dimethylaminopyridine (DMAP). The reaction mixture was stirred at room temperature for 20 hours. Volatile substances were then removed under reduced pressure. The residue was diluted with 250 mL of dichloromethane and washed successively with 100 mL of 1 mol / L hydrochloric acid, 100 mL of distilled water, and 50 mL of brine. The mixed organic extract was dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using 20% ethyl acetate (hexane) as eluent to finally obtain the target compound as a colorless to slightly yellow viscous liquid, which is monomer one of this application.
[0077] In some specific embodiments, the preparation of the aforementioned monomer two is carried out as follows: The preparation method is largely the same as that of monomer one, except that epichlorohydrin is replaced with methyl epichlorohydrin: 100 mmol of 4-methylthiophenethiophenol and 80 mmol of DBU are mixed in 150 mL of toluene (1.41 mol) and added to a 250 mL round-bottom flask equipped with a magnetic stir bar, and stirred for 30 minutes. Subsequently, 10.7 mL of methyl epichlorohydrin (110 mmol) is slowly added dropwise. The reaction vessel is stirred at room temperature for 16 hours. Afterwards, volatiles are removed under reduced pressure, and the residue is diluted with DCM and washed successively with 1 M hydrochloric acid (100 mL), distilled water (100 mL), and brine (50 mL). The mixed organic extract is dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using a mixture of 20% ethyl acetate (EtOAc) in hexane as the eluent, ultimately yielding a colorless, low-viscosity liquid containing 1-(4-methylthiobenzylthiol)-3-chloro-2-methyl-2-propanol.
[0078] 50 mmol of 4',4-dimercaptodiphenyl sulfide was mixed with 8 mL of DBU (53.5 mmol) in 100 mL of toluene (941 mmol) and added to a 250 mL round-bottom flask equipped with a magnetic stir bar. The mixture was stirred for 30 minutes. Subsequently, 9.1 mL of 1-(4-methylthiophenylthiol)-3-chloro-2-methyl-2-propanol (110 mmol) was slowly added dropwise. The reaction vessel was stirred at room temperature for 20 hours. Afterward, the volatiles were removed under reduced pressure, and the residue was diluted with DCM and washed successively with 1 M hydrochloric acid (100 mL), distilled water (100 mL), and brine (50 mL). The mixed organic extract was dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using a mixture of 20% ethyl acetate (EtOAc) in hexane as the eluent, ultimately yielding a pale yellow viscous liquid, which is a liquid of 4,4'-thiobis(1-(4-methylthiophenylthiol)-2-methyl-2-propanol) phenyl sulfide.
[0079] 35 mmol of 4,4'-thiobis(1-(4-methylthiophenylthiol)-2-methyl-2-propanol) phenyl sulfide, 24.3 mL of triethylamine (175 mmol), and 0.4 g of butylated hydroxytoluene (BHT) (1.75 mmol) were added to a 250 mL round-bottom flask equipped with a magnetic stir bar. The solution was diluted with 120 mL (1870 mmol) of dichloromethane and stirred for 30 minutes under argon protection. After cooling the solution to 0 °C, 6.3 mL of acryloyl chloride (77 mmol) was added dropwise under argon protection, followed by 0.4 g of 4-dimethylaminopyridine (DMAP) (3.5 mmol). The reaction mixture was stirred at room temperature for 20 hours. Volatile substances were then removed under reduced pressure. The residue was diluted with 250 mL of dichloromethane and washed successively with 1 mol / L hydrochloric acid (100 mL), distilled water (100 mL), and brine (50 mL). The mixed organic extract was dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using 20% ethyl acetate (hexane) as eluent, finally yielding the target compound as a colorless to slightly yellow viscous liquid, which is the monomer II of this application. The overall synthesis steps can be represented by the following chemical reaction equations:
[0080]
[0081] In some specific embodiments, the preparation of the aforementioned monomer three is carried out as follows: The preparation method is largely the same as that of monomer one, except that acryloyl chloride is replaced with methacryloyl chloride: 100 mmol of 4-methylthiophenethiophenol and 80 mmol of DBU are mixed in 150 mL of toluene (1.41 mol) and added to a 250 mL round-bottom flask equipped with a magnetic stir bar, and stirred for 30 minutes. Subsequently, 110 mmol of epichlorohydrin is slowly added dropwise. The reaction vessel is stirred at room temperature for 16 hours. Afterward, the volatiles are removed under reduced pressure, and the residue is diluted with DCM and washed successively with 1 M hydrochloric acid (100 mL), distilled water (100 mL), and brine (50 mL). The mixed organic extract is dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using a mixture of 20% ethyl acetate (EtOAc) in hexane as the eluent, ultimately yielding a colorless, low-viscosity liquid containing 1-(4-methylthiobenzenethiol)-3-chloro-2-propanol.
[0082] 50 mmol of 4',4-dimercaptodiphenyl sulfide was mixed with 8 mL of DBU (53.5 mmol) in 100 mL of toluene (941 mmol) and added to a 250 mL round-bottom flask equipped with a magnetic stir bar. The mixture was stirred for 30 minutes. Subsequently, 8.2 mL of 1-(4-methylthiophenylthiol)-3-chloro-2-propanol (110 mmol) was slowly added dropwise. The reaction vessel was stirred at room temperature for 20 hours. Afterward, the volatiles were removed under reduced pressure, and the residue was diluted with DCM and washed successively with 1 M hydrochloric acid (100 mL), distilled water (100 mL), and brine (50 mL). The mixed organic extract was dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using a mixture of 20% ethyl acetate (EtOAc) in hexane as the eluent, ultimately yielding a pale yellow viscous liquid containing 4,4'-thiobis(1-(4-methylthiophenylthiol)-2-propanol) phenyl sulfide.
[0083] 35 mmol of 4,4'-thiobis(1-(4-methylthiophenylthiol)-2-propanol)phenyl sulfide, 175 mmol of triethylamine, and 1.75 mmol of butylated hydroxytoluene (BHT) were added to a 250 mL round-bottom flask equipped with a magnetic stir bar. The solution was diluted with 120 mL of dichloromethane and stirred for 30 minutes under argon protection. After cooling the solution to 0 °C, 77 mmol of methacryloyl chloride was added dropwise under argon protection, followed by 3.5 mmol of 4-dimethylaminopyridine (DMAP). The reaction mixture was stirred at room temperature for 20 hours. Volatile substances were then removed under reduced pressure. The residue was diluted with 250 mL of dichloromethane and washed successively with 100 mL of 1 mol / L hydrochloric acid, 100 mL of distilled water, and 50 mL of brine. The mixed organic extract was dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using 20% ethyl acetate (hexane) as eluent, finally yielding the target compound as a colorless to slightly yellow viscous liquid, which is the monomer trioxide of this application. The overall synthesis steps can be represented by the following chemical reaction equations:
[0084]
[0085] In some specific embodiments, the preparation of the aforementioned monomer four is carried out as follows: The preparation method is largely the same as that of monomer one, except that epichlorohydrin is replaced with methyl epichlorohydrin and acryloyl chloride is replaced with methacryloyl chloride. 4-Methylthiobenzylthiophenol (100 mmol) and 12 mL of DBU (80 mmol) are mixed in 150 mL of toluene (1.41 mol) and added to a 250 mL round-bottom flask equipped with a magnetic stir bar, and stirred for 30 minutes. Subsequently, 10.7 mL of methyl epichlorohydrin (110 mmol) is slowly added dropwise. The reaction vessel is stirred at room temperature for 16 hours. Afterwards, volatiles are removed under reduced pressure, and the residue is diluted with DCM and washed successively with 1 M hydrochloric acid (100 mL), distilled water (100 mL), and brine (50 mL). The mixed organic extract is dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using a mixture of 20% ethyl acetate (EtOAc) in hexane as the eluent, ultimately yielding a colorless, low-viscosity liquid containing 1-(4-methylthiobenzylthiol)-3-chloro-2-methyl-2-propanol.
[0086] 50 mmol of 4',4-dimercaptodiphenyl sulfide was mixed with 8 mL of DBU (53.5 mmol) in 100 mL of toluene (941 mmol) and added to a 250 mL round-bottom flask equipped with a magnetic stir bar. The mixture was stirred for 30 minutes. Subsequently, 9.1 mL of 1-(4-methylthiophenylthiol)-3-chloro-2-methyl-2-propanol (110 mmol) was slowly added dropwise. The reaction vessel was stirred at room temperature for 20 hours. Afterward, the volatiles were removed under reduced pressure, and the residue was diluted with DCM and washed successively with 1 M hydrochloric acid (100 mL), distilled water (100 mL), and brine (50 mL). The mixed organic extract was dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using a mixture of 20% ethyl acetate (EtOAc) in hexane as the eluent, ultimately yielding a pale yellow viscous liquid, which is a liquid of 4,4'-thiobis(1-(4-methylthiophenylthiol)-2-methyl-2-propanol) phenyl sulfide.
[0087] 35 mmol of 4,4'-thiobis(1-(4-methylthiophenylthiol)-2-methyl-2-propanol) phenyl sulfide, 24.3 mL of triethylamine (175 mmol), and 0.4 g of butylated hydroxytoluene (BHT) (1.75 mmol) were added to a 250 mL round-bottom flask equipped with a magnetic stir bar. The solution was diluted with 120 mL (1870 mmol) of dichloromethane and stirred for 30 minutes under argon protection. After cooling the solution to 0 °C, 7.5 mL of methacryloyl chloride (77 mmol) was added dropwise under argon protection, followed by 0.4 g of 4-dimethylaminopyridine (DMAP) (3.5 mmol). The reaction mixture was stirred at room temperature for 20 hours. Volatile substances were then removed under reduced pressure. The residue was diluted with 250 mL of dichloromethane and washed successively with 1 mol / L hydrochloric acid (100 mL), distilled water (100 mL), and brine (50 mL). The mixed organic extract was dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography using 20% ethyl acetate (hexane) as eluent, finally yielding the target compound as a colorless to slightly yellow viscous liquid, which is the monomer tetracycline of this application. The overall synthesis steps can be represented by the following chemical reaction equations:
[0088]
[0089] Refractive index testing: Monomers 1, 2, 3, and 4, along with OPPEA (also known as o-phenylphenoxyethyl acrylate, CAS No. 91442-24-9), were dispersed in a solvent such as tetrachloroethane. The dispersed monomers were then spin-coated onto a silicon wafer. After baking, their refractive indices were measured using an ellipsometer. The measured refractive indices were: 1.665 for monomer 1, 1.643 for monomer 2, 1.645 for monomer 3, and 1.638 for monomer 4; the refractive index of OPPEA was 1.575. The optical monomers of this application have refractive indices greater than 1.63, and monomer 1 has a refractive index as high as 1.665. Each optical monomer exhibits a significant improvement in refractive index compared to the comparative example OPPEA.
[0090] Glass transition temperature (Tg) testing. A TA Instruments Japan 2910 differential scanning calorimeter was used to test monomers one, two, three, four, and OPPEA at a heating rate of 10℃ / min. The measured Tg values were 118℃ for monomer one, 113℃ for monomer two, 112℃ for monomer three, 108℃ for monomer four, and 35℃ for OPPEA. The Tg values of the optical monomers in the first component of this application are all greater than 108℃, exhibiting a higher glass transition temperature than OPPEA, indicating that the optical monomers of this application have better heat resistance and stability.
[0091] The types and sources of the second component of the nanoimprint adhesive of this application are described below.
[0092] In some embodiments of this application, the acrylate prepolymer is selected from Kunshan Castel 9537 (specifically purchased from Kunshan Castel Polymer Materials Co., Ltd.); Changxing Materials 6151, Changxing Materials DR-U084, Changxing Materials DR-U299, Changxing Materials DR-U379, ETERCURE DR-U384, Changxing Materials DR-U388, ETERCURE 6371, ETERCURE 6372 (specifically purchased from Changxing Materials Co., Ltd.); Meiyuan HR6100, Meiyuan HR6200, Meiyuan PS4500, Meiyuan PS4040, Meiyuan PS610 (specifically purchased from Meiyuan Special Chemicals Co., Ltd.); at least one of Sartoma CN2254NS, CN2303, CN293, CN750, CN790, CN8008NS, CN8201NS, CN983NS, CN996NS (specifically purchased from Sartoma).
[0093] For example, some of the above materials are UV-curable resins with excellent adhesion, which can be rapidly cured under UV light irradiation; others are multifunctional acrylates, which are convenient for rapid reaction in the photocuring reaction to form a skeleton structure.
[0094] The type and source of the third component of the nanoimprint adhesive of this application are described below.
[0095] In some embodiments of this application, the modified acrylate prepolymer is selected from at least one of Haohui New Materials CR91000, Haohui New Materials CR91093, Haohui New Materials CR90223, Haohui New Materials HU280 (specifically purchased from Guangdong Haohui New Materials Co., Ltd.); and Lankeluo L-6902X, Lankeluo L-6901, and Lankeluo L-6902 (specifically purchased from Guangdong Lankeluo New Materials Co., Ltd.).
[0096] For example, some of the modified acrylate prepolymers are nano-hybrid modified polyurethane acrylates with multiple functionalities, which improve the rapid curing ability of nanoimprint adhesives; some are special functional group acrylates with high leveling properties, yellowing resistance and water resistance, and good toughness. As a component of nanoimprint adhesives, they can improve the coating convenience of nanoimprint adhesives and prevent yellowing; some are inorganic hybrid polyurethane acrylate resins with high reactivity, high crosslinking density, low shrinkage, good scratch resistance and wear resistance, and high hardness. As a component of nanoimprint adhesives, they can improve the wear resistance of nanoimprint adhesives after curing.
[0097] The type and source of the fourth component of the nanoimprint adhesive of this application are described below.
[0098] In some embodiments of this application, the nanoparticles are metal oxide nanoparticles. Metal oxide nanoparticles can improve the structural stability of the nanoimprint adhesive after imprinting, making it less prone to collapse during demolding and etching processes.
[0099] In some embodiments of this application, the particle size range of the nanoparticles is 10nm to 20nm, for example, values of 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 18nm, and 20nm. Nanoparticles within the above range can not only disperse quickly in the solution, reducing entanglement between polymers, but also maintain the viscosity within a certain range, making the entire colloid easy to coat. Furthermore, the nanoparticles can be embedded in the cross-linking network of optical monomers, which can increase the hardness of the entire cured nanoimprint adhesive, which is beneficial to improving Young's modulus and preventing the collapse of the micro-nano structures on the nanoimprint adhesive during demolding.
[0100] In some embodiments of this application, the nanoparticles are metal oxide nanoparticles with a particle size range of 10 nm to 20 nm. The specific technical effects can be referred to the above description and will not be repeated here.
[0101] In a further embodiment, the nanoparticles are titanium dioxide nanoparticles or zirconium oxide nanoparticles. Titanium dioxide can absorb ultraviolet light, protecting the stability of the imprinting adhesive during ultraviolet curing. Titanium dioxide has a refractive index of 2.2–2.6, which can significantly increase the refractive index of the nanoimprinting adhesive even with a small amount added. Zirconia has high stability and a refractive index of 2.1–2.3, and can also rapidly increase the refractive index of the nanoimprinting adhesive even with a certain amount added.
[0102] In a specific embodiment, the nanoparticles are selected from PixClear Zirconia 10nm, PixClear Titania 20nm, and One or more of the core-shell 20nm process, without limitation.
[0103] The fifth component of the nanoimprint adhesive of this application is described below, along with its type and source.
[0104] In some embodiments of this application, the photoinitiator is selected from photoinitiator 1173 (i.e., 2-hydroxy-2-methyl-1-phenyl-1-propanone), photoinitiator 1176, photoinitiator 184 (i.e., 1-hydroxy-cyclohexyl-phenyl ketone), TPO (i.e., (2,4,6-trimethylbenzoyl chloride)diphenylphosphine oxide), TPO-L (i.e., ethyl 2,4,6-trimethylbenzoylphosphonate), photoinitiator 127 (i.e., 2-hydroxy-1-(4-(2-hydroxy-2-methylpropionylphenyl)benzyl)-2-methyl-1-propanone), photoinitiator 369, ITX, BDK (i.e., benzoin dimethyl ether), photoinitiator 819 (i.e., phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide), photoinitiator 754, photoinitiator 380, BMF, and ANTHRACURE. TM UVS-1331, ANTHRACURE TM At least one of UVS-1101, Easepi 6992, Easepi 1176, and Easepi 250.
[0105] For example, the photoinitiators provided above can all adjust the curing rate and degree of curing of nanoimprint adhesives. By selecting different photoinitiators, nanoimprint adhesives can be cured under light of different wavelengths. For instance, (2,4,6-trimethylbenzoyl chloride)diphenylphosphine oxide (also known as TPO) has an absorption wavelength of 350 nm to 400 nm. After light irradiation, it can generate two free radicals, benzoyl and phosphoryl, both of which can initiate polymerization. It has a fast photocuring speed, low volatility, non-yellowing coating, low polymerization effect, and no residue, and can be used in transparent layer structures. Ethyl 2,4,6-trimethylbenzoylphosphonate (also known as photoinitiator TPO-L) has an absorption wavelength of 270 nm to 370 nm. 2-Hydroxy-2-methyl-1-phenyl-1-propanone (also known as photoinitiator 1173) has an absorption wavelength of 244 nm. It is a liquid product, easy to blend, and easy to combine with other photoinitiators. It is highly efficient, has low yellowing, and exhibits some volatility at high temperatures. Benzoin dimethyl ether (also known as photoinitiator BDK) has an absorption wavelength of 205 nm to 253 nm. It is a highly efficient and stable photoinitiator, with stronger absorption performance compared to 1173 and 184, thus more effectively promoting the cross-linking reaction of double bonds. 2-Hydroxy-1-(4-(2-hydroxy-2-methylpropionylphenyl)benzyl)-2-methyl-1-propanone (also known as photoinitiator 127) has an absorption wavelength of 259 nm. It has low oxygen sensitivity, good surface curing effect, low volatility, and low odor from both its own odor and photolysis products.
[0106] The type and source of the sixth component of the nanoimprint adhesive of this application are described below.
[0107] In some embodiments of this application, the coupling agent is at least one of γ-(methacryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriethoxysilane, γ-(methacryloyloxy)propyltriethoxysilane, methacryloyloxymethyltriethoxysilane, 3-methacryloyloxypropyltri(methoxyethoxy)silane, methacryloyloxypropyltri(dimethylsiloxane)silane, γ-(acryloyloxy)propyltrimethoxysilane, γ-(acryloyloxy)propyltriethoxysilane, allyltri(trimethylsiloxy)silane, 1,3-bis(3-methacryloyloxypropyl)tetra(trimethylsiloxy)disiloxane, and N-(3-acryloyloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane.
[0108] For example, the organosilanes provided above can all promote adhesion to the substrate, prevent the adhesive film from detaching from the substrate during the imprinting process, prevent the migration of free coupling agents, and effectively reduce the probability that the cured nanoimprint adhesive will be peeled off from the substrate during demolding.
[0109] The type and source of the seventh component of the nanoimprint adhesive of this application are described below.
[0110] In some embodiments of this application, the diluent is at least one of propylene glycol methyl ether acetate, dipropylene glycol methyl ether acetate, ethyl acetate, N,N-dimethylformamide, methyl ethyl ketone, dimethyl sulfoxide, and butyl acetate.
[0111] For example, the diluents mentioned above are all organic solvents. The diluents can make the components evenly dispersed. The organic solvents can also adjust the viscosity and evaporation rate of the nanoimprint adhesive, thereby making it easier to control the thickness and surface smoothness of the film during spin coating.
[0112] The preparation method of the nanoimprint adhesive in the foregoing embodiments of this application will now be described.
[0113] According to the present invention, a method for preparing nanoimprint adhesive based on the foregoing embodiments is provided, such as... Figure 5 As shown, it includes the following steps:
[0114] Step S210: Add the diluent to the container, and add the optical monomer, acrylate prepolymer, and modified acrylate prepolymer to the protective gas. Stir and mix to form a homogeneous first solution. The types and molar ratios of the optical monomer, acrylate prepolymer, modified acrylate prepolymer, and diluent can be referred to the previous text and will not be repeated here.
[0115] In step S210 of some embodiments, a first stirring speed of 400 r / min to 600 r / min can be used during stirring, for example, values such as 400 r / min, 450 r / min, 500 r / min, and 600 r / min. This allows the components to mix slowly, preventing agglomeration and enabling the components to disperse quickly and evenly.
[0116] In step S210 of some embodiments, the temperature in the container is 21°C to 25°C, for example, it can be 21°C, 22°C, 23°C, 24°C and 25°C, so that the various components are mixed more gently and are less likely to decompose.
[0117] In step S210 of some embodiments, the stirring time is 20 min to 40 min, for example, it can be 20 min, 30 min and 40 min, so that the components are fully mixed and uniform.
[0118] In step S210 of some embodiments, during the process of stirring and mixing evenly, gases such as nitrogen, argon, or helium can be introduced into the container to reduce the oxygen concentration inside the container. The specific choice can be made according to the actual situation.
[0119] Step S220: Stir the first solution and add the coupling agent and photoinitiator, then continue stirring to form a homogeneous second solution. The types, amounts, and functions of the coupling agent and photoinitiator are described above and will not be repeated here.
[0120] In step S220 of some embodiments, a first stirring speed of 700 r / min to 900 r / min can be used during stirring, for example, values such as 700 r / min, 750 r / min, 800 r / min, 850 r / min, and 900 r / min. This allows the coupling agent and photoinitiator to be dispersed more quickly and uniformly.
[0121] In step S220 of some embodiments, the temperature in the container is 21°C to 25°C, for example, it can be 21°C, 22°C, 23°C, 24°C and 25°C, so that the mixing is more gentle and less prone to decomposition during the process of adding components.
[0122] In some embodiments, in step S220, the stirring time is 20 min to 40 min, for example, it can be 20 min, 30 min and 40 min, so that the components are fully mixed and uniform.
[0123] In step S220 of some embodiments, during the process of stirring and mixing evenly, gases such as nitrogen, helium or argon can be introduced into the container to reduce the oxygen concentration inside the container. The specific gas to be introduced can be selected according to the actual situation.
[0124] Step S230: Add nanoparticles to the second solution and continue stirring until homogeneous, then let it stand. The types, particle sizes, and functions of the nanoparticles are as described above and will not be repeated here.
[0125] In step S230 of some embodiments, the temperature in the container is 21°C to 25°C, for example, it can be 21°C, 22°C, 23°C, 24°C and 25°C, so that the mixing is relatively gentle during the process of adding nanoparticles and the temperature of the system before and after is consistent.
[0126] In step S230 of some embodiments, the stirring time is 10h to 14h, for example, it can be 10h, 11h, 12h, 13h and 14h, so that the nanoparticles are fully dispersed in the system.
[0127] In step S230 of some embodiments, the settling time is 20 min to 40 min, for example, it can be 20 min, 30 min and 40 min.
[0128] Step S240: Obtain nano-imprint adhesive by pressurized filtration and encapsulation.
[0129] In some embodiments of this application, the pressure filtration encapsulation uses a 0.22 μm organic filter membrane to filter out impurities and obtain the nanoimprint adhesive of this application.
[0130] As can be seen from the above, the preparation method of the nanoimprint adhesive proposed in this invention produces a nanoimprint adhesive in which the components are fully mixed, do not easily agglomerate, and can form a relatively uniform coating adhesive, which is convenient for subsequent coating and imprinting. The prepared nanoimprint adhesive is easy to use and ensures that it has the aforementioned properties of nanoimprint adhesive.
[0131] The preparation method of the nanoimprint adhesive of this application and the performance test of the obtained nanoimprint adhesive are described below with reference to specific embodiments.
[0132] Example 1
[0133] 40g of propylene glycol methyl ether acetate (PGMEA) was added to a container, protected with nitrogen, and stirred at 500 rpm. Then, 15g of optical monomer, 8g of HR6200 acrylate prepolymer, and 8g of CR91000 modified acrylate prepolymer were slowly added, and the mixture was stirred for 30 minutes to ensure complete dispersion and dissolution, resulting in a homogeneous first solution. The liquid temperature in the container was maintained at 23°C throughout the process. The optical monomer used was the aforementioned monomer one, with the structural formula [structural formula would be inserted here].
[0134] Adjust the rotation speed to 800 r / min, then slowly add 1 g of γ-(methacryloyloxy)propyltrimethoxysilane coupling agent and 3 g of TPO photoinitiator, and continue stirring for 30 minutes to completely disperse and dissolve the system to obtain a uniform second solution. During the process, maintain the liquid temperature in the container at 23°C.
[0135] Slowly add 25g of PixClear Zirconia 10nm nanoparticle dispersion and continue stirring for 12 hours, maintaining the liquid temperature in the container at 23°C during the process. After stirring is complete, let stand for 30 minutes.
[0136] Semi-transparent to semi-transparent nanoimprint adhesives can be obtained by pressurizing and encapsulating a 0.22μm organic filter membrane.
[0137] Example 2
[0138] The preparation method is largely the same as in Example 1, except that the optical monomer is replaced with a structure having the following structural formula: Monomer II was used to obtain nanoimprint adhesive.
[0139] Example 3
[0140] The preparation method is largely the same as in Example 1, except that the optical monomer is replaced with a structure having the following structural formula: Monomer III was used to obtain nanoimprint adhesive.
[0141] Example 4
[0142] The preparation method is largely the same as in Example 1, except that the optical monomer is replaced with a structure having the following structural formula: Monomer IV was used to obtain nanoimprint adhesive.
[0143] Comparative Example 1
[0144] The preparation steps are largely the same as in Example 1, except that the optical monomer in Example 1 is replaced with o-phenylphenoxyethyl acrylate (OPPEA) to prepare the ultraviolet nanoimprint adhesive. The OPPEA monomer does not have the phenyl sulfide group or the S atom of this application.
[0145] Test case
[0146] The nanoimprint enamel prepared in Examples 1-4 and the UV nanoimprint enamel prepared in Comparative Example 1 were subjected to the following performance tests, and the test methods are as follows:
[0147] 1. Appearance Test
[0148] A certain amount of the nanoimprint adhesive prepared in Examples 1 to 4 and the ultraviolet nanoimprint adhesive prepared in Comparative Example 1 were poured into colorless and transparent glass bottles respectively, and the appearance characteristics of the adhesive were observed under white light or natural light.
[0149] 2. Viscosity test
[0150] The refractive index of the nanoimprint adhesives prepared in Examples 1-4 and the ultraviolet nanoimprint adhesive prepared in Comparative Example 1 at 20°C was tested on a Brookfield rheometer.
[0151] 3. Solid content test
[0152] The nanoimprint adhesives prepared in Examples 1-4 and the ultraviolet nanoimprint adhesives prepared in Comparative Example 1 were weighed on an analytical balance, and then baked in a forced-air drying oven at 120°C for 2 hours. The weight of the baked adhesives was measured and their solid content was calculated.
[0153] 4. Hardness test
[0154] The nanoimprint adhesives prepared in Examples 1-4 and the ultraviolet nanoimprint adhesives prepared in Comparative Example 1 were spin-coated onto silicon wafers according to certain parameters. After baking, they were exposed and imprinted on an imprinting device to form a uniform film layer with a thickness of 1μm to 3μm. The hardness of the film was tested using a nanoindenter.
[0155] 5. Young's modulus test
[0156] The nanoimprint adhesives prepared in Examples 1-4 and the ultraviolet nanoimprint adhesives prepared in Comparative Example 1 were spin-coated onto silicon wafers according to certain parameters. After baking, they were exposed and imprinted on an imprinting device to form a uniform film layer with a thickness of 1-3 μm. The Young's modulus was tested using a nanoindenter.
[0157] 6. Surface water droplet angle test
[0158] The nanoimprint adhesives prepared in Examples 1-4 and the ultraviolet nanoimprint adhesives prepared in Comparative Example 1 were spin-coated onto silicon wafers according to certain parameters. After baking, they were exposed and imprinted on an imprinting device to form a uniform film layer with a thickness of 1-3 μm. The surface water droplet angle was measured using a water droplet angle meter.
[0159] 7. Refractive index test
[0160] The nanoimprint adhesives prepared in Examples 1-4 and the ultraviolet nanoimprint adhesives prepared in Comparative Example 1 were spin-coated onto silicon wafers according to certain parameters. After baking, they were exposed and imprinted on an imprinting device to form a uniform film layer with a thickness of 1-3 μm. The refractive index was measured using an ellipsometer.
[0161] The final measured performance parameters are compared in Table 1 below.
[0162] Table 1 Performance test results of Examples 1-4 and Comparative Example 1
[0163]
[0164] The measured performance data shows that the nanoimprint adhesive prepared using optical monomers in this application has a higher refractive index than the ultraviolet nanoimprint adhesive prepared using OPPEA. The refractive index of the optical monomers in this application is higher than that of OPPEA. Compared with the ultraviolet nanoimprint adhesive prepared using OPPEA under the same preparation conditions, the nanoimprint adhesive prepared using the optical monomers in this application has a higher refractive index after curing. Therefore, this application can obtain a higher refractive index with the addition of the same amount of nanoparticles. In contrast, Comparative Example 1 requires the use of more nanoparticles to achieve the same refractive index as this application. The nanoimprint adhesive with optical monomers in this application can control the amount of nanoparticles added within a suitable range while ensuring that the nanoimprint adhesive has the required high refractive index after curing. This results in a nanoimprint adhesive with good flowability and easy coating.
[0165] Compared to the UV nanoimprinting adhesive of Comparative Example 1, the Young's modulus of the nanoimprinting adhesive of this application is significantly improved, indicating that the nanoimprinting adhesive with optical monomer components of this application can significantly improve its own structural strength. During the imprinting and demolding process, the formed micro-nano structure is not easily damaged, which can ensure a certain production yield and reduce the residual adhesive on the mold, making it convenient for the mold to be reused.
[0166] Meanwhile, the viscosity of the nanoimprint adhesive of this application is slightly higher than that of Comparative Example 1, but the overall viscosity is lower. The nanoimprint adhesive of this application has good fluidity and is easy to coat, which is conducive to filling micro-nano structures to form high-precision patterns. Moreover, the adhesive is easy to adhere to the substrate and is not easy to peel off from the substrate during demolding. It is easy to process and use, and is matched with efficient imprinting process to improve efficiency and facilitate large-scale mass production.
[0167] The droplet angle of the nanoimprint adhesive in this application is smaller than that of the UV nanoimprint adhesive in the comparative example, indicating that the nanoimprint adhesive in this application is easier to spread and coat, has good wetting and leveling properties on the substrate, excellent uniform coating performance, more uniform coating, high appearance yield after imprinting, and easier removal of hydrophilic contaminants on the surface of the adhesive.
[0168] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A nanoimprinting adhesive, characterized in that, The nanoimprint adhesive is prepared from the following raw materials: optical monomers, acrylate prepolymers, modified acrylate prepolymers, nanoparticles, photoinitiators, coupling agents, and diluents. The general structural formula of the optical monomers is as follows: Wherein, R1 is methyl or hydrogen, R2 is methyl or hydrogen, and the difference between the refractive index of the nanoparticle and the refractive index of the optical monomer is greater than 0.
4.
2. The nanoimprint adhesive as described in claim 1, characterized in that, The weight parts of each component in the raw material are as follows: 10 to 20 parts of optical monomers; 5 to 10 parts of acrylate prepolymer; 5 to 10 parts of modified acrylate prepolymer; 20-35 parts nanoparticles; 3 to 5 parts of photoinitiator; 1 to 5 parts coupling agent; Diluent: 15 to 55 parts.
3. The nanoimprint adhesive as described in claim 1 or 2, characterized in that, The optical monomer is prepared using the following steps: 4-Methylthiobenzylthiophenol, the first catalyst and the first solvent are mixed evenly, and epichlorohydrin or methyl epichlorohydrin is added to react and generate the first product, which is 1-(4-methylthiobenzylthiool)-3-chloro-2-propanol or 1-(4-methylthiobenzylthiool)-3-chloro-2-methyl-2-propanol. 4',4-dimercaptodiphenyl sulfide, a second catalyst, and a second solvent are mixed evenly, and a first product is added to catalyze a reaction to generate a second product. The molar ratio of the first product to 4',4-dimercaptodiphenyl sulfide is (2~2.4):
1. The second product is 4-4'-thiobis(1-(4-methylthiophenylthiol)-2-propanol) phenyl sulfide or 4-4'-thiobis(1-(4-methylthiophenylthiol)-2-methyl-2-propanol) phenyl sulfide. The second product, auxiliaries, and stabilizers are added to the third solvent and mixed thoroughly. The solution is cooled, and under gas protection, acryloyl chloride or methacryloyl chloride is added to react with the third catalyst to produce a product with the following general structural formula: The optical monomer, wherein the molar ratio of acryloyl chloride or methacryloyl chloride to the second product is (2~2.4):
1.
4. The nanoimprint adhesive as described in claim 3, characterized in that, The first catalyst and the second catalyst are selected from at least one of 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,5-diazabicyclo[4.3.0]non-5-ene and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene; The first solvent and the second solvent are selected from at least one of toluene, dimethyl sulfoxide, N,N-dimethylformamide and acetonitrile; The adjuvant is selected from triethylamine or 1,8-diazabicycloundec-7-ene; The stabilizer is selected from at least one of butylated hydroxytoluene, butylated hydroxyanisole and tert-butylhydroquinone; The third solvent is selected from dichloromethane or tetrahydrofuran; The third catalyst is 4-dimethylaminopyridine.
5. The nanoimprint adhesive as described in claim 3, characterized in that, The molar ratio of 4-methylthiobenzylthiophenol, the first catalyst, the first solvent, and epichlorohydrin is 100:(70~90):(1317~1505):(100~120); or, the molar ratio of 4-methylthiobenzylthiophenol, the first catalyst, the first solvent, and methyl epichlorohydrin is 100:(70~90):(1317~1505):(100~120). The reaction temperature of 4-methylthiobenzylthiophenol with epichlorohydrin or methyl epichlorohydrin is room temperature, and the reaction time is 14h~18h. The molar ratio of the 4',4-dimercaptodiphenyl sulfide, the second catalyst, the second solvent, and the first product is 50:(50~55):(847~1035):(100~120). The reaction temperature of the 4',4-dimercaptodiphenyl sulfide with the first product is room temperature, and the reaction time is 18h~22h; The molar ratio of the second product, auxiliary agent, stabilizer, third solvent, methacryloyl chloride, and third catalyst is 35:(144~187.2):(1.5~2.0):(1714~2026):(70~84):(3.0~4.0); or the molar ratio of the second product, auxiliary agent, stabilizer, third solvent, methacryloyl chloride, and third catalyst is 35:(144~187.2):(1.5~2.0):(1714~2026):(70~84):(3.0~4.0); The second product reacts with acryloyl chloride or methacryloyl chloride at 0°C or under ice bath conditions, and under a protective atmosphere containing nitrogen or an inert gas.
6. The nanoimprinting adhesive as described in claim 1 or 2, characterized in that, The acrylate prepolymers are selected from Kunshan Castel's 9537; Changxing Materials 6151, Changxing Materials DR-U084, Changxing Materials DR-U299, Changxing Materials DR-U379, Changxing Materials DR-U384, Changxing Materials DR-U388, Changxing Materials 6371, and Changxing Materials 6372; The following are some of the following: Midea HR6100, Midea HR6200, Midea PS4500, Midea PS4040, Midea PS610; and at least one of the following: Sartoma CN2254NS, CN2303, CN293, CN750, CN790, CN8008NS, CN8201NS, CN983NS, CN996NS.
7. The nanoimprint adhesive as described in claim 1 or 2, characterized in that, The modified acrylate prepolymer is selected from at least one of Haohui New Materials CR91000, Haohui New Materials CR91093, Haohui New Materials CR90223, Haohui New Materials HU280; and Lankeluo L-6902X, Lankeluo L-6901 and Lankeluo L-6902.
8. The nanoimprinting adhesive as described in claim 1 or 2, characterized in that, The nanoparticles are metal oxide nanoparticles, and / or the particle size range of the nanoparticles is 10 nm to 20 nm.
9. The nanoimprinting adhesive as described in claim 8, characterized in that, The nanoparticles are titanium oxide nanoparticles or zirconium oxide nanoparticles.
10. The nanoimprinting adhesive as described in claim 1 or 2, characterized in that, The photoinitiator is selected from at least one of photoinitiator 1173, photoinitiator 1176, photoinitiator 184, TPO, TPO-L, photoinitiator 127, photoinitiator 369, ITX, BDK, photoinitiator 819, photoinitiator 754, BMF, ANTHRACURE™ UVS-1331, ANTHRACURE™ UVS-1101, Easepi 6992, and Easepi 250.
11. The nanoimprinting adhesive as described in claim 1 or 2, characterized in that, The coupling agent is at least one of γ-(methacryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriethoxysilane, γ-(methacryloyloxy)propyltriethoxysilane, methacryloyloxymethyltriethoxysilane, 3-methacryloyloxypropyltri(methoxyethoxy)silane, methacryloyloxypropyltri(dimethylsiloxane)silane, γ-(acryloyloxy)propyltrimethoxysilane, γ-(acryloyloxy)propyltriethoxysilane, allyltri(trimethylsiloxy)silane, 1,3-bis(3-methacryloyloxypropyl)tetra(trimethylsiloxy)disiloxane, and N-(3-acryloyloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane.
12. The nanoimprint adhesive as described in claim 1 or 2, characterized in that, The diluent is at least one of propylene glycol methyl ether acetate, dipropylene glycol methyl ether acetate, ethyl acetate, N,N-dimethylformamide, methyl ethyl ketone, dimethyl sulfoxide, and butyl acetate.
13. A method for preparing a nanoimprint adhesive as described in any one of claims 1 to 12, characterized in that, The steps include: adding a diluent to a container, adding optical monomers, acrylate prepolymers and modified acrylate prepolymers to a protective gas, stirring and mixing to form a homogeneous first solution; Stir the first solution and add the coupling agent and photoinitiator, then continue stirring to form a homogeneous second solution; Add nanoparticles to the second solution and continue stirring until homogeneous, then let stand. Nanoimprint adhesive was obtained by pressurized filtration and encapsulation.
14. The method for preparing the nanoimprint adhesive as described in claim 13, characterized in that, During the reaction, the temperature in the container is 21℃~25℃; the pressurized filtration encapsulation uses a 0.22μm organic filter membrane.
Citation Information
Patent Citations
Thiol-ene ultraviolet light curing nano imprinting material
CN103279011A
Photosensitive composition, cured product and method for producing cured product
CN114746808A